Back to (a different) emigration? Mobility from Spain and Italy during the economic crisis - Caro, Raquel; Cavasola, Silvia; Fernández, Mercedes (Iberoamerican Journal of Development Studies, 2018)
The economic crisis has had a very severe impact on the economic situation of both Spain and Italy, whose employment figures fell by record levels, affecting all population categories, especially the youngest cohorts. This situation had a profound impact on the dynamics of migration in these two (traditionally emigrant-sending turned emigrant-receiving) countries, with a rising of emigration in the face of decreasing immigration. The main goal of this study is to compare Spanish and Italian emigration mechanisms through secondary sources. We lean toward the hypothesis that both countries, Spain and Italy, could have changed their migration patterns due to the economic crisis. For this purpose, we undertake a cross-national comparative analysis of stock and flow data on emigrations during the economic downturn (2009-2015).
Keywords: emigration; Spain; Italy; Economic Crisis; comparative perspective; Southern Europe